PETITE TIMBER STRUCTURES IN/AND ARCHITECTURAL DESIGN EDUCATION - Karanakov, Bojan; Ivanovski, Jovan (International Journal - Wood, Design & Technology, Vol.10,No.1.(2021):14-24, 2021)
ABSTRACT Тhe aim of this paper is to present a recent educational experience developed through the ongoing pedagogical process at the Faculty of Architecture in Skopje, exploring the advantages of informal tools of education, with particular focus on the learning-by-building method of learning architectural design. The main goal of the teaching experience explored in the paper was to get architecture students acquainted with the great potentials of timber as architectural building material. The paper specifically focuses on presenting four case studies, documenting the development of different timber structures of high architectural quality, designed and built by architecture students. Each architectural structure was realized within the educational, pedagogical, social, cultural and representational framework of the International Summer School of Architecture, an architectural workshop that for 30 consecutive years has been organized by the Faculty of Architecture at Ss. Cyril and Methodius University in Skopje. The International Summer School of Architecture was established in 1992, and has since then been a place for teaching and learning architecture for more than 500 domestic and international students and more than 100 architects and teachers from all around the world. In the 30 years of its existence the International Summer School of Architecture has shown the ability to transform and adapt its format to numerous pedagogical viewpoints and concepts, from highly theoretical to applicative ones. As many as four International Summer School sessions have been realized exploring the learning-by-building methodology, as result of which several timber structures were designed and built on various locations by the students and their tutors. The collection of timber structures presented in the paper represents not only a valuable portfolio of the International Summer School of Architecture of the Faculty of Architecture in Skopje, but a significant source of knowledge for studying architecture design methodologies, processes and strategies, as well as engineering and construction techniques and their role in the architectural design education on university level.
Keywords: architectural design education, learning tools, learning-by-building method, timber